Pengaruh Beban Kerja Berlebih Terhadap Kinerja Pegawai di Lembaga Pemasyarakatan Perempuan Kelas IIA Palembang - Frischa Mentari Safrin; Kusmiyanti Kusmiyanti (Coopetition : Jurnal Ilmiah Manajemen, 2022)
Work-overload on employees is generally caused by the irrelevant basic education they already have, so that many of them work not according to competence. Of the 98 employees, 22 of them have not attended the training. Some of the employees, still work more than the working hours every month. This has a bad impact on performance which causes employees to come late every month. The purpose of this study is to determine whether work-overload has a positive effect on employee performance. This study took the locus of the Class IIA Palembang Women's Correctional Institution. The population used is all employees as many as 98 people. Using a sampling technique, the total sampling because the population is less than 100 people. Collecting data using a questionnaire given to each employee online. Data analysis used multiple linear regression test with SPSS 26. The results showed that variable X had a positive effect on variable Y, with an R square value of 70.3%. This study found the regression equation Y = 11.261 + 0.863X, which means that this regression equation is directly proportional because the value of the coefficient b has a positive value.